Tackling urban disparities through participatory culture-led urban regeneration. Insights from Lisbon - Falanga, Roberto (2021)
In the last few decades, the diffusion of culture-led urban regeneration schemes has intercepted the growth of participatory approaches across a wide range of policy domains. Partnerships between private and public agencies have sought, accordingly, the engagement of citizens and stakeholders to push forward context-specific interventions. From the participatory action research developed in Lisbon, one of the cities funded under the EU-funded project ROCK, we analyse the ways in which this project has tackled spatial divides and socioeconomic inequalities in the project demonstration area. Our main argument is that operational decisions and substantive mismatches have given rise to opportunities and bottlenecks throughout the implementation of the project. While the public investment has been directed to regenerate a deprived area, it has fallen short of promoting greater connections within the area and with the surrounding neighbourhoods. ROCK’s actions have only partially met local community expectations regarding the project’s objectives for the optimisation of tangible and intangible cultural heritage, with impacts over degrees of citizen engagement in the local Living Lab.